Ukuran Perusahaan Memoderasi Pengaruh Profitabilitas, Free Cash Flow, dan Likuiditas pada Kebijakan Dividen - Wahyuni, Made Dita; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 30 No 4 (2020)DO - 10.24843/EJA.2020.v30.i04.p19, 2020)
Dividend policy is the company's decision to determine whether profits derived by the company will be distributed to shareholders in the form of dividends or will be used as retained earnings. Companies must pay attention to factors in determining dividend policy. This study aims to analyze the iinfluence of the effect of profitability, free cash flow, and liquidity on dividend policy with firm size as a moderating variable. This research was conducted at infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange in 2016-2018. The sample research method used was purposive sampling. The data analysis technique used is Moderated Regression Analysis. Based on the results of the study, it is known that profitability and firm size do not affect dividend policy, meanwile free cash flow and liquidity have a positive effect on dividend policy. This study also found that firm size can strengthen the effect of profitability, free cash flow, and liquidity on dividend policy. Keywords: Profitability; Free Cash Flow; Liquidity; Dividend Policy; Firm Size.